Pulmonary complications in patients undergoing neurointensive care - Skodvin, Øyvind Øygard (UiT Norges arktiske universitet, 2018)
Respiratory complications frequently develop in patients with acute brain injury (ABI), and contribute considerably to poor neurologic outcome and increased mortality in these patients. Several reports have shown that respiratory failure may account for as many as 50% of the deaths after brain injury. We wanted to take a closer look at respiratory complications in patients with ABI at our hospital, and conducted a small study focusing on three aims. These were 1) to assess the incidence of respiratory failure in neurointensive patients of the University Hospital of North Norway (UNN) in Tromsø, 2) to examine whether the PEEP/FiO2 values used here are similar to the ARDS Network recommendations for PEEP/FiO2 settings and 3) to assess the tidal volumes (TVs) set to ventilate these patients in controlled ventilator modes. Materials and methods: The study was conducted as a retrospective observational study. Tracheally intubated patients with acute traumatic brain injury (TBI) and subarachnoid hemorrhage (SAH) admitted to the ICU of UNN Tromsø between the 1st of January and the 31st of December 2016 were included. Results: Eighteen patients with SAH and 12 patients with TBI were identified. Sixteen patients (53%) were diagnosed with any pulmonary complication. Twelve patients (40%) were diagnosed either with pneumonia or were suspected to have developed pneumonia. Seven patients (23%) were diagnosed with atelectasis, while one patient (3%) had a pleural effusion. Compared to the ARDS Network recommendation for PEEP/FiO2 settings, too low PEEP values for a given FiO2 were identified in 6 (20%) of the patients. The mean (±SD) TV/actual body weight (n=28) was 6,7 ± 1,1 mL/kg, while the mean (±SD) TV/PBW (n=17) was 7,3 ± 1,0. Conclusion: The present study found a high incidence of pulmonary complications in ICU patients with ABI, with pneumonia as the most common cause. This finding is consistent with other studies investigating this group of patients. None of the patients in our material were diagnosed with ARDS. The ...